Rare Isolated Trapezium Fracture: Clinical Case Presentation - Pedro Martins Branco (Gazeta Médica, 2022)
Isolated trapezium fractures are rare, accounting for 0.4% of the hand injuries. As these injuries are often imperceptible on plain radiographs, diagnosis in the Emergency Department setting is challenging. Computed tomography scan can be helpful in the diagnosis. The gold standard treatment for trapezium fractures is still debatable. A 54 years-old male patient presented to an Emergency Department following a motorcycle accident. He reported pain and swelling on the radial half of his left non-dominant hand. Radiographs were inconclusive. Computed tomography scan and magnetic resonance imaging revealed an isolated trapezium fracture with a non-displaced small volar fragment. To our best knowledge, this fracture pattern has not been reported before. Conservative treatment resulted in union with excellent thumb function and no complications. This case highlights the importance of a high clinical suspicion, careful history taking, physical examination, and imaging interpretation to avoid missing a trapezium fracture.